The Effectiveness of Multicultural Communication in Child Development at the Early Age of Buah Hati in Kapuas District - Lisnawati (Sinergi International Journal of Communication Sciences, 2023)
This research departs from the social reality of the Kapuas community, which has cultural, ethnic and linguistic diversity. In this context, multicultural communication is an important aspect of early childhood learning and social interaction. The effectiveness of multicultural communication in this study is defined as the extent to which cross-cultural interactions can enhance children's social, emotional, and cognitive development in a heterogeneous environment. This study aims to analyze the role of multicultural communication in shaping early childhood character by examining key indicators such as increased adaptability, empathy, and social interaction. The results show that children actively engaging in cross-cultural interactions have better adaptability in various social situations, show higher empathy towards peers from different cultural backgrounds, and have more effective communication skills. In addition, this study offers a new perspective in understanding the role of multicultural communication in early childhood development, especially in areas with high levels of cultural heterogeneity. Previous studies have focused more on early childhood education in general without highlighting how multicultural communication plays a role in children's interaction and learning from an early age. The conclusion of this study emphasizes the importance of implementing multicultural communication in educational and family settings. Therefore, educators and parents are advised to create an environment that supports multicultural communication through joint play activities, cross-cultural discussions, and the use of diverse media as interactive learning tools. Thus, children can grow up in an inclusive environment and have strong social skills early on. This study uses descriptive qualitative methods and data collection techniques such as interviews, observation, and documentation. Multiculturalism plays an important role in improving the effectiveness of early childhood social and emotional skills. Early on, children exposed to cross-cultural interactions have better social adaptability and show higher empathy in interactions with peers from different cultural backgrounds. Multicultural communication's effectiveness was shown to positively impact early childhood social and emotional development in Kapuas district. This finding confirms the importance of implementing diversity-based communication strategies in early childhood education to improve children's social skills and readiness to face heterogeneous environments.